AGROFORESTRY SYSTEMS BASED ON LAND SUITABILITY IN SOCIAL FORESTRY AREAS IN BARRU REGENCY, SOUTH SULAWESI - Ariandi, Rahmat; Akbar, Akbar; Ichsan, Muhammad; Sabri, Ahmad; Mukti, Jauhar (Gorontalo Journal of Forestry Research, 2025)
Selecting appropriate plant species based on land suitability evaluation is essential for developing sustainable agroforestry systems in Social Forestry regions. This study assessed land suitability in the Social Forestry area of Barru Regency, South Sulawesi, Indonesia (04°06?–04°47? S; 119°32?–119°49? E). Data were obtained from six sampling points through field observations, soil analysis, and farmer interviews. Parameters analyzed included soil pH, organic carbon, texture, erosion hazard, and water availability. Land suitability classification was based on the FAO framework and supported by GIS mapping. Limiting factors such as nutrient retention (nr), rooting media (rc), and erosion hazard (fh) were evaluated to determine current and potential suitability classes. Results indicated considerable variability across sites. Soil pH was acidic (4.18–6.26), organic carbon ranged from 1.71% to 2.30%, and soils were mainly loam to sandy clay loam. The landscape was characterized by steep slopes (25–45%) and elevations of 150–450 m above sea level. Most areas were classified as marginally suitable (S3), though improvements such as liming, organic matter addition, and erosion control could enhance suitability to moderately suitable (S2). Proposed agroforestry designs combine primary crops coffee, candlenut, aren palm, mahogany, and durian with complementary species including cacao, rambutan, and sengon. These combinations are expected to balance production, conservation, and shade functions according to site conditions. This study emphasizes the role of land evaluation in optimizing agroforestry planning within social forestry landscapes. Findings provide practical recommendations for integrating ecological sustainability with community-based resource management.